2005
DOI: 10.1111/j.0300-9475.2005.01537.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased Frequency of Antral CD4+ T and CD19+ B Cells in Patients with Helicobacter pylori‐Related Peptic Ulcer Disease

Abstract: Only a fraction of Helicobacter pylori (HP)-infected individuals develop clinical disease. Recent research indicates that immunological mechanisms may be important for understanding the pathophysiology of HP infection. Differences in the individual cellular immune response may reflect the clinical diversity. The aim of the present study was to investigate the cellular immune response against HP in three clinically well-defined patient groups: HP-positive peptic ulcer, HP-positive and HP-negative gastritis. Bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 22 publications
4
12
0
2
Order By: Relevance
“…Therefore, there was an inversion in the CD4/CD8 ratio in LPMC (~1:3) compared to PBMC (~3:1). These results confirmed and extended those reported by others (16, 19, 20) by showing that these differences were observed in all age groups (Figure 3B). When CD4 + T cells in LPMC of children and the elderly were compared to adults, children showed a significantly higher frequency of these cells (Figure 3B).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Therefore, there was an inversion in the CD4/CD8 ratio in LPMC (~1:3) compared to PBMC (~3:1). These results confirmed and extended those reported by others (16, 19, 20) by showing that these differences were observed in all age groups (Figure 3B). When CD4 + T cells in LPMC of children and the elderly were compared to adults, children showed a significantly higher frequency of these cells (Figure 3B).…”
Section: Resultssupporting
confidence: 93%
“…Consistent with previous reports, the frequency of CD3 + cells was lower as a percentage of total LPMC cells in the gastric mucosa than in PBMC (19, 31). Additionally, CD4 + and CD8 + T cells from gastric LPMC were found at similar frequencies as reported by others (14, 16) and the vast majority of gastric CD8 + and CD4 + T cells showed a T EM phenotype (CD62L − , CD45RA − ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, this study characterized the relative frequency of the different CD19 þ subsets in peripheral blood. We found that compared to uninfected subjects, H. pylori infection is associated with expansion of these cells in line with the previous observations (23,24). Importantly, however, we now report that this increase is at least partly mediated by increase in the PDCA-1 þ B-cell compartment.…”
Section: Discussionsupporting
confidence: 93%
“…In addition to macrophages, T-and B-lymphocytes were recruited in the wake of inflammatory response (26). Our gene expression microarray analysis of H. pylori-infected WT and Ctsx Ϫ/Ϫ epithelial cells revealed B-and T-cell specific gene expression signatures that clearly discriminated from uninfected cells.…”
Section: Discussionmentioning
confidence: 82%